A educação ambiental em escolas do município de Uberlândia (MG) - Ferreira, Maria Luiza (2023)
This study aimed to understand how Environmental Education is addressed in elementary education in municipal schools in the city of Uberlândia (MG). To this end, a bibliographical review on the topic was prepared, analysis of the Class Plans/Annual Planning of Elementary School teachers, analysis of the Municipal Education Plan (PME); analysis of Decree No. 19,642, of March 9, 2022; analysis of the Guidelines for Schools' Pedagogical Actions in 2022, together with the letters issued by the Department of Education/CEMEPE. As a result, this study points to the need for improvements in the approaches to Environmental Education in the municipal network of the city of Uberlândia (MG), with the aim of enforcing the guidelines present in the Municipal Education Plan, in Decree nº. 19.642/2022, as well as the guidelines set out in the municipal document “Guidelines for Pedagogical Actions in Schools”. This study also points to the need for greater investments and actions aimed at the continued training of teaching professionals who work in the municipality's initial grades, which consider the nuances of the social, cultural, historical, economic and political dimensions of a critical and reflective Environmental Education in the educational process.